The Influence of Work Professionalism in Realized Employee Performance through Transformational Leadership and Work Motivation as Intervening Variables in Toyota Dealership in Central Jakarta - Nita Maryati; Jubery Marwan; Zahera Mega Utama (Journal of Center for Energy Policy and Human Resources Capacity Development, 2025)
The purpose of this research is to investigate the impact that professionalism in the workplace has on employee performance, with transformational leadership and work motivation serving as the factors that act as mediators. The research was carried out at Toyota stores in Jakarta, and it utilized a quantitative technique in conjunction with an explanatory planning approach. All of the primary data were examined to determine their validity, reliability, homogeneity, and normality, and the sampling method that was utilized was saturated sampling. For the purpose of analyzing the connections between the variables, path analysis was utilized. According to the findings, professionalism in the workplace has a substantial impact, both directly and indirectly, on transformational leadership, employee performance, and motivation in the workplace both directly and indirectly. Additionally, workplace motivation and transformational leadership both have been shown to have a favorable impact on the performance of employees. Based on these findings, it appears that individuals that exhibit professionalism by demonstrating knowledge, competence, attitude, and a strong work ethic, in conjunction with high motivation and transformational leadership, are more likely to attain optimal performance.